АҚБӨКЕН ЦЕНУРОЗЫНЫҢ ПАТОМОРФОЛОГИЯСЫ - А. Мауланов; Г. Кузембекова; Д. Калкаева; Қ. Жуманов; А. Жылқайдар; Л. Бесембаева; Г. Мухпулова (Animal Health and Biosafety, 2026)
This article presents the clinical manifestations, pathological-anatomical findings, and histological changes associated with coenurosis in saiga antelope. Coenurosis is a chronic parasitic disease characterized by damage to the central nervous system, pressure atrophy of brain tissue, and impaired motor coordination. The increasing saiga population in Kazakhstan emphasizes the importance of monitoring parasitic diseases in wild ungulates. The study material consisted of carcasses of 2 saiga antelopes aged 8–9 months that died after showing clinical signs suspected of coenurosis at the Almaty Zoo. Complete pathological-anatomical examination was performed. Tissue samples from the brain, liver, kidneys, heart, lymph nodes, spleen, and intestine were collected for histological examination and fixed in 10% neutral buffered formalin. Paraffin sections were stained with hematoxylin and eosin and examined using light microscopy. According to anamnestic data, the affected saiga antelopes showed unsteady gait, head pressing against obstacles, isolation from healthy animals, stiffness of the neck muscles, ocular hyperemia, eyelid swelling, and nystagmus. Necropsy revealed a large coenurus cyst in the frontal region of the brain. The surrounding brain tissue was atrophied, and the skull bone over the affected area was thinned due to pressure. Histological examination revealed non-suppurative parasitic encephalitis, hemorrhagic foci, proliferation of glial cells, formation of a fibrous capsule, and destructive changes in brain tissue. Additional findings included dystrophic changes in the liver and kidneys, venous hyperemia and edema in the lungs, and chronic catarrhal enteritis in the small intestine. The findings indicate that the main morphological feature of coenurosis in saiga antelope is the presence of a coenurus cyst in the brain, accompanied by pressure-induced atrophic and inflammatory changes. Future studies should include parasitological and molecular methods to identify the causative agent more accurately.